2019
DOI: 10.7455/ijfs.v8i2.614
|View full text |Cite
|
Sign up to set email alerts
|

Development and incorporation of nanoemulsions in food

Abstract: Currently, nanoencapsulation of bioactive compounds is promising, and is one of the methods that has been proven very effective. The development of food-grade nanoemulsions is in a state of constant innovation due to the interesting features that this method of encapsulation has, such as small droplet size, kinetic stability and appearance. With this technology, it is possible to control some food properties, such as texture, taste and stability. In this article, we present a review of the most commonly used m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Bioactive compounds were found to conserve antioxidant and antimicrobial activities by an encapsulation process, such as the water/oil (W/O) nanoemulsion, which involves a transparent or translucent system with a particle size ranging from 10 to 100 nm; these compounds are thermodynamically unstable and are produced by high-energy methods, such as high shear agitation, high homogenization, and high ultrasound pressures. They were shown to improve bioavailability and avoid instability, especially when are exposed to diverse environmental conditions [ 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bioactive compounds were found to conserve antioxidant and antimicrobial activities by an encapsulation process, such as the water/oil (W/O) nanoemulsion, which involves a transparent or translucent system with a particle size ranging from 10 to 100 nm; these compounds are thermodynamically unstable and are produced by high-energy methods, such as high shear agitation, high homogenization, and high ultrasound pressures. They were shown to improve bioavailability and avoid instability, especially when are exposed to diverse environmental conditions [ 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…A potential advantage of these dispersions is that they have high compatibility with the components of foods and can even cross biological membranes without difficulty [8,10]. Nanoemulsions have been used mainly in the development of some foods and beverages to contribute to the stability of the foods that contain them [11]. Zambrano-Zaragoza et al [12] studied the effect of a coating with α-tocopherol and cactus mucilage that were applied on apples and found that the nanoemulsion helped to maintain the firmness of the apples and decreased the activity of certain enzymes in the fruits.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 represents the formation of nanoemulsions. Low-energy methods include the method of spontaneous emulsification, phase inversion composition, phase inversion temperature, and high-energy methods include high-pressure homogenization, microfluidizer homogenization, and ultrasonication [38].…”
Section: Methods Of Formation Of Nanoemulsionsmentioning
confidence: 99%
“…In this method, the emulsion is pumped through a small orifice and droplets of emulsion are rotating again and again inside the equipment in order to achieve the optimum droplet size. Afterward, with the effect of high shear on the emulsion droplets, it leads to the formation of nanoemulsions [38]. Microfluidizer, in mechanical terms, is similar to a high-velocity static mixer which does not constitute any movable joints.…”
Section: Microfluidizer Homogenizationmentioning
confidence: 99%